Evaluation of effiecincy of A. parasiticus Spear on larval instars of the mosquito Culex quinquefasciatus Say (Diptera culicida) - Sarah Nair Aljumaily; Mohammed R. Annon Alhasnawy (Al-Qadisiyah Journal of Pure Science, 2018)
Ensure that current research test the efficiency of the mushroom A. parasiticus in combat phases mosquito, Culex quinquefasciatus, have influenced the concentrations of suspended mushrooms and metabolites secondary raw in phases larval of a mosquito, as it gave the commentator al-Fitr at the concentration 1 Ã— 610 spore / ml highest percentage loss of larvae homicide rate reached the first phase larval 69% after 120 hours, while the loss ratio was 31.66% at the lower concentration 1 Ã— 410 spore / ml during the period of time itself. As for the effect of the secondary metabolites of raw mushroom A. parasiticus was the percentage of the loss of the first phase at the top focus 100% and within 72 hours was 81.66%, while the loss ratio at the lowest concentration of 25% and during the same time period 45%.